Governmental Controls and the Theory of International Trade and Finance - Whittlesey, Charles R. (Quarterly Journal of Economics, 1936)
Degrees of governmental interference in international trade and finance, 90.— Effect of rigid governmental control on the basic principles of international trade and finance, 93.— Generalizations derived from the principle of the balance of payments, 97.— The case of less extreme control, 103.— Segmentation of prices, 104.